2007
DOI: 10.1097/hjh.0b013e3282efeb7e
|View full text |Cite
|
Sign up to set email alerts
|

Effects of antihypertensive drugs on blood pressure and proteinuria in childhood

Abstract: The blood pressure reduction of angiotensin-converting enzyme inhibitors, angiotensin II receptor antagonists and calcium-channel blockers is almost identical. In children with pathological proteinuria angiotensin-converting enzyme inhibitors or angiotensin II antagonists are superior to calcium-channel blockers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
6

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 87 publications
(123 reference statements)
1
22
0
6
Order By: Relevance
“…It is in agreement with a recent pediatric metaanalysis showing that the BP reduction by ACEI, angiotensin-receptor blockers and CCB is almost identical. 21 It is also in good agreement with the data from adults showing that in obesity-related PH no one class of antihypertensive agents is superior to others. 22 The recent United States and European guidelines recommend that children with PH can be treated with all classes of antihypertensives.…”
Section: Association Of Bp Control With Target Organ Damagesupporting
confidence: 78%
“…It is in agreement with a recent pediatric metaanalysis showing that the BP reduction by ACEI, angiotensin-receptor blockers and CCB is almost identical. 21 It is also in good agreement with the data from adults showing that in obesity-related PH no one class of antihypertensive agents is superior to others. 22 The recent United States and European guidelines recommend that children with PH can be treated with all classes of antihypertensives.…”
Section: Association Of Bp Control With Target Organ Damagesupporting
confidence: 78%
“…From a strict evidence-based medicine perspective, the trial was designed to compare blood pressure targets and all subjects received a fixed dose ACE inhibitor, so to conclude that proteinuria reduction (and ACE inhibitors) were responsible for better outcomes, this analysis would need to be adjusted for blood pressure achieved. Two additional small uncontrolled studies and one systematic review in children with CKD also showed reduction in hypertension and proteinuria, with agents blocking the renin-angiotensin system [39][40][41]. More importantly, while only a small study, one controlled trial, compared an ARB with a calcium channel blocker in children with CKD and found a similar reduction in blood pressure with both agents, but a greater reduction in proteinuria with the ARB [42].…”
Section: First-line Antihypertensive Medicationmentioning
confidence: 94%
“…Although non-pharmacological options should be considered, drug treatment remains the mainstay of antihypertensive management in all stages of CKD. The different classes of antihypertensive agents are comparable with respect to their BP-lowering efficacy in children with CKD (228,229), but most of the available clinical evidence has been obtained with drugs blocking the renin-angiotensin system (RAS) (25,228,230). They have a powerful, dosedependent antiproteinuric action in pediatric nephropathies (231).…”
Section: Non-diabetic Renal Diseasementioning
confidence: 99%